Menemukan Prinsip Etika Lingkungan Hidup di Hutan Larangan Pahewan Hulu, Desa Bawan - Yuliana . (Jurnal Sosiologi Andalas, 2021)
The ecological crisis is a serious environmental problem today. Solutions are sought to overcome these problems. Dialogue to find solutions from the government continues, while indigenous peoples have implemented ways to manage nature carefully to prevent environmental problems. Indigenous peoples have long practiced ways to protect nature, through the attitude of managing nature (forests, rivers, etc.) carefully. This attitude is known as ethics towards nature, or environmental ethics. By using a qualitative research method with a constructivist approach, the purpose of this paper is to examine the attitude of the indigenous people of Bawan Village in the form of Pawan Huluk local wisdom. Pawan Huluk is a forbidden forest, a forest whose existence is respected by the indigenous people of Bawan Village. The respectful attitude of the Bawan Village community towards the forest is a form of environmental ethics.